2017
DOI: 10.1038/am.2017.161
|View full text |Cite|
|
Sign up to set email alerts
|

Cargo–carrier interactions significantly contribute to micellar conformation and biodistribution

Abstract: Strategies to deliver drugs using nanocarriers, which are passively or actively targeted to their alleged site of action might favorably affect benefit-risk profiles of novel therapeutics. Here we tested the hypothesis whether the physico-chemical properties of the cargo as well as the actual conditions during encapsulation interfere during formulation of nanoparticular cargo-carrier systems. On the basis of previous work, a versatile class of nanocarriers is polyether-based ABC triblock terpolymer micelles wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Cargo-carrier interactions signicantly contributed to the properties of encapsulated drugs and their localization within the micelles. 91…”
Section: Applicationsmentioning
confidence: 99%
“…Cargo-carrier interactions signicantly contributed to the properties of encapsulated drugs and their localization within the micelles. 91…”
Section: Applicationsmentioning
confidence: 99%
“…Whereas inhibition of PI3Kγ could be a strategy to counter liver failure, the same signaling molecule might confer protection in other organs, e.g., in the heart ( 20 ). This highlights the need to achieve organ and cell-specific targeting of these processes in multi-organ dysfunction ( 21 , 22 ).…”
Section: End Organ Failure—insights From Systems Medicinementioning
confidence: 99%
“…Hence, before signaling mediators can be used therapeutically, it will be necessary to overcome the significant hurdles posed by these multifunctional signaling molecules. Nanoparticle-based targeted drug-delivery ( 21 , 22 , 59 ) might help to specifically tackle this problem.…”
Section: Outlook—purposeful Manipulation Of Signals Mediating Damage mentioning
confidence: 99%
“…Unfortunately, there is minimum information discussing the effect of interaction between a drug and its matrix to its release profile, specifically for the matrix in the form of a hard-shell capsule. Press et al [2] reported that polyether-based triblock tricopolymer micelles act as an agent to give the effect to the physicochemical properties of the matrix as well as the actual conditions during encapsulation interfere during the formulation of nanoparticular drug-matrix systems. On the other hand, drug molecules may directly interact with matrix molecules, lowering their solubility and/or retarding their release from the matrixes [1,3].…”
Section: ■ Introductionmentioning
confidence: 99%